(untitled) (Universal xalqaro ilmiy jurnal, 2026)
n this article it will explore the relationship between pragmatics and word meaning with a focus on Modern English, and how meaning is influenced not only by grammatical form, but also by context, speaker intention, and social interaction. Whereas traditional semantics considers meaning as a stable property of words and sentences, pragmatics emphasizes that meaning is negotiated in actual communicative contexts. The paper takes as its goal to provide a close analysis of such critical pragmatic concepts as context, deixis, implicature, presupposition, and speech acts, showing how those ideas influence the interpretation of lexical meaning in everyday communication. One point of particular focus with which he brings attention is that of dynamic word meanings in modern English—most especially in digital discourse, media, and intercultural communication. The study shows that understanding word meaning demands not just dictionary definitions but an understanding also of norms and attitudes in society, one’s cultural background, and of communicative aims—often based upon examples from actual usage. The relative importance of pragmatics in explaining implicit meanings of speakers, and how listeners interpret them successfully. In an attempt to establish a conclusion, the article argues that pragmatics is a defining factor and is relevant in modern English through word meanings; pragmatics is one of the major theories in both modernism and modern Western English which is needed for efficient communication, linguistic analysis etc